The Principle and Foundation of the Spiritual Exercises of Saint Ignatius of Loyola (Hekima Review, 2013)
In our postmodern world fully engulfed by science and technological development, the question of human origin, purpose of our being on earth and the beatific vision (ultimate end) are threefold question that should hunt every man and woman. To pretend that these questions are not there or, that they have no signifi-cance on one’s life seems to me as an illusion. Undoubtedly, many live their lives; fulfil their day-to-day activities “as if” the contemporary style of living and choosing in our world today is already a norm. In this essay, the ‘Principle and Foundation’ of the Spiritual Exercises of Saint Ignatius of Loyola offer us a medium to dialogue and to reflect over these questions.